Análise de sistemas ambientais aplicada ao planejamento: estudo em macro e mesoescala na região da bacia hidrográfica do rio Apodi - Mossoró, RN/ Brasil - Carvalho, Rodrigo Guimarães de (2011)
This thesis had as its main objective the analysisof the environmental systems of the Apodi-Mossoró river watershed, in macro and mesoscales, as a way to subsidize environmental planning. It is known that the scale under which integrated environmental studies are developed outlines the reach and deepening of results, impacting directly on the environmental planning process that may be adopted. The macro scale (1:250,000) approach was used to the study of the Apodi-Mossoró river watershed, with an approximate area of 15,500 sqKm. On the other hand, the mesoscale (1:40,000) approach focused the municipality of Grossos, situated on the lower course of the watershed, with an area of 126 sqKm. Methodological procedures used the systemic approach as their guiding axle. Among the most important stages, we may highlight the survey of bibliographic and documentary material about the area of study, the survey of geo-mapping material, field research, analysis and mapping of environmental systems, formulation of thematic indexes and environmental zoning. It was noted, regarding the environmental planning of Apodi-Mossoró river watershed, that the size of the area and the amount of existing municipalities leverages the use of multi-thematic indexes as tools for environmental diagnosis. The results of the analysis enable an appraisal of guidelines for the environmental macroplanning. In the case of the municipality of Grossos, the analysis on a scale of greater detail enables a better understanding of the environment and greater cartographic accuracy, which favors the establishment of anenvironmental zoning proposal. It is noticed that, for being a large territorial dimension watershed, the environmental planning shall be developed at both the macro and mesoscales. In macro scale, general guidelines shall guide and indicate the measures to be takento improve the socio-economic and environmental sustainability within a vision of wholeness. The municipalities, in turn, shall promote diagnostics with a greater level of detail, thus allowing the implementation of local zoning in line with the propositions reached in macroplanning.